2018
DOI: 10.1128/aac.00637-17
|View full text |Cite
|
Sign up to set email alerts
|

Population Pharmacokinetics of Cefotaxime and Dosage Recommendations in Children with Sickle Cell Disease

Abstract: The pharmacokinetic profile of most drugs is dependent on the patient's covariates and may be influenced by the disease. Cefotaxime is frequently prescribed in pediatric patients with sickle cell disease (SCD), characterized by vaso-occlusive complications, chronic hemolytic anemia, and a defective immunological function predisposing the individual to severe infection. Data on the impact of the disease on the disposition of cefotaxime are missing. In the present study, our aims were to determine cefotaxime pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 34 publications
3
8
0
Order By: Relevance
“…For amoxicillin, our review showed that the median clearance in the pediatric population are in accordance with previously reported values in critically ill adults (0.10 L/h/kg vs 0.13 L/kg) (63). Whereas for amoxicillin and cefotaxime, we observed a value of clearance divided by 2.0 for cefotaxime and 3.0 for ampicillin in the pediatric population (21,22,24,31,39,41,47,50). But if we looked at each amoxicillin studies in detail, we observed a large variability on amoxicillin clearance values as for piperacillin, explained by the same maturation process described previously (61) since numerous studies have been conducted in preterms and neonates (22,24,47,50).…”
Section: Discussionsupporting
confidence: 91%
“…For amoxicillin, our review showed that the median clearance in the pediatric population are in accordance with previously reported values in critically ill adults (0.10 L/h/kg vs 0.13 L/kg) (63). Whereas for amoxicillin and cefotaxime, we observed a value of clearance divided by 2.0 for cefotaxime and 3.0 for ampicillin in the pediatric population (21,22,24,31,39,41,47,50). But if we looked at each amoxicillin studies in detail, we observed a large variability on amoxicillin clearance values as for piperacillin, explained by the same maturation process described previously (61) since numerous studies have been conducted in preterms and neonates (22,24,47,50).…”
Section: Discussionsupporting
confidence: 91%
“…Impaired hepatic and renal blood flow has been linked to elevated morphine clearance in SCD patients, 29 and to impaired lidocaine metabolism 30 . The large differences in clearance and volume of distribution is also consistent with the results of several studies that have shown differences in PK parameters between SCD and non-SCD populations for various drugs: the clearance of ciprofloxacin is reported to be 89% higher in SCD patients compared to non-SCD patients; 31 cefotaxime clearance has been shown to be higher in SCD patients, and higher still in SCD patients with acute chest syndrome; 32 and morphine clearance is reported to be 3-10 fold higher in SCD patients compared to published estimates in the non-SCD population 29 . The chronic inflammation in SCD may also induce drug metabolism, as demonstrated for codeine in SCD patients 33 .…”
Section: Discussionsupporting
confidence: 84%
“…For malarial sickle cell disease, autopsies showed that nearly one-half of 300 had died of infections (Manci et al 2003). Effective treatments for sickle cell allele carriers (Maksoud et al 2018) will help maintain these and other adverse genes. Moreover, the expansion of neonatal intensive care units (NICUs) after 1950 has increased survival of low-birth weight babies (Drevenstedt et al 2008).…”
Section: Longevity Genes and Gxementioning
confidence: 99%